2020
DOI: 10.3389/fpsyg.2020.565503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Emotional and Cognitive Regulation of Young People in a Lockdown Situation Due to the Covid-19 Pandemic

Abstract: Background: In a situation of compulsory home isolation enacted by governments at the spreading of the Covid-19 pandemic, the emotional health and well-being of students became a key factor in the successful implementation of distance teaching methodologies in face-to-face education universities. Psychological well-being, an essential factor in preventing academic failure, has been threatened in this serious situation of unprecedented and stressful isolation. The aim of this study is to analyze the students' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 30 publications
1
55
0
5
Order By: Relevance
“…Thus, for example, the positive restructuring coping strategy played a relevant role in the RNA when analyzing its standardized importance. In this line, a previous research concluded that those coping strategies of a cognitive nature were essential in the processes of adaptation and effective personal adjustment, especially when they focused the positive side of the situation or, at least, attempted to show a positive attitude ( Fernández-Cruz et al, 2020 ). Studies prior to confinement also found a relationship between the use of certain strategies, problem-solving focus, and lower stress levels in undergraduates ( Keech et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for example, the positive restructuring coping strategy played a relevant role in the RNA when analyzing its standardized importance. In this line, a previous research concluded that those coping strategies of a cognitive nature were essential in the processes of adaptation and effective personal adjustment, especially when they focused the positive side of the situation or, at least, attempted to show a positive attitude ( Fernández-Cruz et al, 2020 ). Studies prior to confinement also found a relationship between the use of certain strategies, problem-solving focus, and lower stress levels in undergraduates ( Keech et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cultural factors mediated the use of these strategies; thus, a study conducted in Pakistan with 1,134 university apprentices concluded that religion was the most widely employed coping strategy during COVID-19, followed by acceptance, self-destruction, and other active coping techniques ( Salman et al, 2020 ). In another research involving over 80 Spanish-speaking universities in 13 different countries, cognitive strategies were key to adapting to the new situation of isolation, including the ability to seek its positive aspects ( Fernández-Cruz et al, 2020 ). Similarly, in pre-covid periods, statistically significant positive relationships had also been found between the engagement in avoidant behaviors -through technological means- and perceived stress ( Oliva et al, 2018 ), as well as negative relationships between higher social support and lower stress levels in young university students ( Erschens et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CC/COVID-19 adaptation of Cruz [30] is an instrument that was designed specifically for this study. It focuses on discovering the beliefs of university students about the pandemic and the housing conditions of the place where they spent their home confinement.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…Given all the aforementioned information, it is clear that there is a wide range of references in the literature showing that psychological well-being is a factor that can affect persistence and early university dropout possibilities, and that the lockdown situation can cause stress [23,30,39]. We believe that this is a good time to analyze and compare the emotional cognitive regulation of students from mainland Spanish universities with that of students from the Universidad de Las Palmas de Gran Canaria.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation